Clinicopathological and Molecular Characterization of Metastatic Gastrointestinal Stromal Tumors with Prolonged Benefit to Frontline Imatinib. (20th August 2018) - Serrano, César; García‐del‐Muro, Xavier; Valverde, Claudia; Sebio, Ana; Durán, José; Manzano, Aránzazu; Pajares, Isabel; Hindi, Nadia; Landolfi, Stefania; Jiménez, Laura; Rubió‐Casadevall, Jordi; Estival, Anna; et al.
Abstract: Background: Oncogenic KIT/PDGFRA signaling inhibition with imatinib achieves disease control in most patients with advanced/metastatic gastrointestinal stromal tumor (GIST), but resistance eventually develops after 20–24 months. Notably, a small subset of these patients obtain durable benefit from imatinib therapy. Methods: We analyzed clinical, pathological, and molecular characteristics and long‐term outcomes in patients with metastatic GIST treated with continuous daily dosing of frontline imatinib in a cohort of patients benefiting for ≥5 years. A control group was obtained from the national Spanish Group for Sarcoma Research database and used as comparator. Results: Sixty‐four imatinib long‐term responders (LTRs) and 70 control cases were identified. Compared with controls, LTRs at baseline had better performance status (PS) 0–1 (100% vs. 81%), lower mitotic count (median, 8 vs. 15), and tumor burden (number of metastases, 3 vs. 7). KIT exon 11 was the only region found mutated in LTRs. LTRs achieved 34% complete responses and a median progression‐free survival of 11 years, compared with 4% and 2 years, respectively, in the control cohort. Prognostic factors that independently predicted long‐term benefit with imatinib were PS, number of metastases prior to imatinib, and response to imatinib. Fifteen LTR patients developed new side effects attributable to imatinib after ≥5 years of continuous treatment. No resistance mutations were found in metastatic samples from three patients progressing on imatinib. Conclusion: GISTs in LTRs are a distinctive entity with less aggressive behavior and marked sensitivity to KIT inhibition. Patients reaching 5 or more years on imatinib have a higher chance of remaining progression free over time. Abstract : This article identifies distinctive clinicopathological and molecular features in long‐term responders to imatinib treatment compared with patients with gastrointestinal stromal tumors reaching the usual median progression‐free survival. Clinical insights from this subgroup collected during the long‐term follow‐up are also provided.